A low-cost commercial Cu(ii)–EDTA complex for electrocatalytic water oxidation in neutral aqueous solution. Issue 92 (31st October 2022) - Yu, Kaishan; Sun, Yue; Zhu, Dingwei; Xu, Ziyi; Wang, Jiayi; Shen, Junyu; Zhang, Qijian; Zhao, Wei
Abstract : A low-cost commercial Cu complex [Cu(EDTA)(H2 O)] is developed as a molecular catalyst for OER with high efficiency and durable stability. Abstract : Herein, we choose a commercial Cu complex [Cu(EDTA)(H2 O)] (EDTA = ethylene diamine tetraacetic acid) as a molecular catalyst for water oxidation to avoid complex synthesis and lower catalyst cost. [Cu(EDTA)(H2 O)] could catalyze the water oxidation reaction efficiently under neutral conditions with an overpotential of 684 mV, a k cat of 8.03 s −1 and good stability in the long-term electrolysis. Our finding is of great significance for the development of stable, rapid, and easily accessible catalysts for water oxidation.